Binding of a nuclear protein to the rat growth hormone silencer element. - Roy, R J (1992)
The rat growth hormone (rGH) gene is uniquely expressed in a subset of cells from the anterior pituitary. This strongly cell type specific expression is controlled by both cis-acting positive sequences that bind the pituitary specific transcription factor Pit-1 and cis-acting negative regulatory elements that lie upstream of the Pit-1 sites. The negative elements act to prevent expression of the gene in inappropriate cell types. Here we report that the most proximal rGH silencer element is specifically bound by a protein found in a number of rGH non-expressing cell types and which exerts a negative regulatory effect through the recognition of this rGH element in transient transfection assays. The sequence recognized by this protein is similar to sequences of several other negative regulatory elements as well as to the consensus binding site for the transcription factor NF1. However, the 45 KDa molecular weight identified for this protein does not correspond to any of the sizes previously reported for NF1 suggesting that it is likely to represent a new member amongst this family of transcription factors.